Federal programmes and projects as a means of engaging the population in physical education and sport - Demyanova, L.M.; Mavropulo, O.S.; Tashchiya, A.A.; Zhiharev, D.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to analyse the effectiveness of regional mechanisms for involving the population of the Russian Federation in regular physical education and sports activities. Methods and structure of the study. The research was conducted using a comprehensive approach based on an analysis of statistical data from the Russian Ministry of Sport and Rosstat, a comparative analysis of physical culture and sports development indicators, and an analysis of data from sociological surveys of the population conducted by the All-Russian Centre for Public Opinion Research and Counter-Training Centre ‘Platform’ between 2020 and 2024. Results and conclusions. Scientific research has shown that in recent years there have been significant differences between regions in terms of the level of physical activity among the population. The gap between the leading regions and the outsiders is almost twofold, which indicates the need to develop more flexible, targeted measures for the development of physical culture and sport, taking into account the characteristics and potential of each region. Among the most effective tools for encouraging the population to engage in regular sports activities, several areas can be identified, first and foremost the comprehensive development of accessible sports infrastructure, the systematic organisation of mass physical education and sports events, the use of public-private partnership mechanisms, the active introduction of digital services, and the adaptation of sports programmes to different age and social groups of the population.